(untitled) (Journal of Comparative & International Higher Education, 2023)
This study compares Canadian and Iranian international students’ conceptions of critical thinking during their graduate studies in Canada. Critical thinking is an essential skill in Canadian higher education. It enables students to make reasoned judgments from their observations and experimentation. This narrative inquiry using open-ended interviews describes the narratives of eight students from different master’s programs at a university in western Canada to examine their experiences and notions of critical thinking. The preliminary findings reveal that while all Canadian participants had knowledgeable perspectives about critical thinking, Iranian participants required more knowledge to build their critical thinking conceptualizations. Moreover, content knowledge, instructors’ competence, and teaching methods significantly influenced students’ critical thinking development. Results offer a comprehensive understanding of how Canadian higher institutions and curriculum developers need to provide appropriate opportunities and curricula for cultivating and developing critical thinking among local students while paying attention to Iranian students’ needs and academic preparedness.